Characterization and activity of CuMnOx/γ-Al2O3 catalyst for oxidation of carbon monoxide. (June 2017) - Dey, Subhashish; Dhal, Ganesh Chandra; Mohan, Devendra; Prasad, Ram
Graphical abstract: Abstract: The addition of γ-Al2 O3 support into the CuMnOx catalyst enhances the dispersion capacity as compared to unsupported CuMnO x catalysts. There exist strong interactions between the copper, manganese oxide and γ-Al2 O3 support. The effect of γ-Al2 O3 on the dispersion, active states and reduction behavior of surface supported CuMnOx catalysts have been investigated by X-ray diffraction (XRD), Fourier transforms infrared spectroscopy (FTIR), Scanning electron microscopy with energy-dispersed X-ray (SEM-EDX) and Brunauer Emmett Teller (BET) analysis. The characterization results confirm that Cu +, Mn 2+ and Al mostly existed on the effective surface sites of the CuMnOx/γ-Al2 O3 catalysts. These results indicate that there is a synergistic interaction between the copper, manganese and aluminum oxide, which is responsible for the high catalytic activity of CO oxidation reactions. In the CuMnOx/γ-Al2 O3 catalysts, the 40%CuMnOx/γ-Al2 O3 catalyst shows the highest catalytic activity for complete oxidation of CO at 130 °C temperature. The main aim of this paper is to find the optimum percentage of γ-Al2 O3 support into the CuMnOx catalyst for total oxidation of CO at a low temperatures. Using γ-Al2 O3 support in the CuMnOx catalyst lowers the cost without sacrificing the performance.